51g+20g-61g-6g-3g-1=61

Simple and best practice solution for 51g+20g-61g-6g-3g-1=61 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 51g+20g-61g-6g-3g-1=61 equation:


Simplifying
51g + 20g + -61g + -6g + -3g + -1 = 61

Reorder the terms:
-1 + 51g + 20g + -61g + -6g + -3g = 61

Combine like terms: 51g + 20g = 71g
-1 + 71g + -61g + -6g + -3g = 61

Combine like terms: 71g + -61g = 10g
-1 + 10g + -6g + -3g = 61

Combine like terms: 10g + -6g = 4g
-1 + 4g + -3g = 61

Combine like terms: 4g + -3g = 1g
-1 + 1g = 61

Solving
-1 + 1g = 61

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 1g = 61 + 1

Combine like terms: -1 + 1 = 0
0 + 1g = 61 + 1
1g = 61 + 1

Combine like terms: 61 + 1 = 62
1g = 62

Divide each side by '1'.
g = 62

Simplifying
g = 62

See similar equations:

| (2cosx)(-sinx)=0 | | 54/44 | | 1/9(x-6) | | 0=-1/2a-2/3 | | 3x+6=8x+34 | | -3c-(-86c)+6=89 | | x+3y=55 | | 42=-6(-3n+6)+6(n-3) | | y=6x-26 | | 3.5x+14=42 | | -81w-11w-9w+23w-w+6=85 | | 47/X=6-1/X | | 3a^2=6x | | 20+w=32 | | (2y+8)(2y+8)=0 | | 30p-11p+15p-29p=90 | | -6+2(5-4x)=22-2x | | -6(-2x+2)+4(3+4x)=28 | | 10xt=1.8654 | | (a+6)(a^2-8a+8)=0 | | 6m^2+66m+121=0 | | 3.0=0.4m-2+0.2m | | 8w-3w-4w-1=32 | | (7y)^1/3 | | 10xt= | | 5x+10+x=-8 | | (5x+3)(2x-6)=0 | | px^2+qx+r=(x+1)(2x-7) | | 3x-2=x*x | | 3s-2s-1=29 | | 79=-7k | | 34/36 |

Equations solver categories